2001
DOI: 10.1375/bech.18.3.135
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Supervision in Four Mental Health Professions: A Review of the Evidence

Abstract: This paper examines a range of theoretical issues and the empirical evidence relating to clinical supervision in four mental health professions, namely clinical psychology, occupational therapy, social work, and speech pathology. Despite the widespread acceptance of the value of supervision among practitioners and the large quantity of literature on the topic, there is very little empirical evidence in this area. It is not clear whether supervision actually produces a change in clinician behaviour, nor whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
161
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(166 citation statements)
references
References 80 publications
(108 reference statements)
2
161
0
3
Order By: Relevance
“…Like Spence et al,(2001) they found little evidence concerning the outcomes of supervision, but concluded that there was emerging evidence about the aspects of supervision valued by supervisees − specifically availability, positive relationships, mutual communication, support and delegating responsibility. Skillful supervisors with expertise who were able to provide practical support were particularly appreciated.…”
Section: Previous Reviewsmentioning
confidence: 99%
See 2 more Smart Citations
“…Like Spence et al,(2001) they found little evidence concerning the outcomes of supervision, but concluded that there was emerging evidence about the aspects of supervision valued by supervisees − specifically availability, positive relationships, mutual communication, support and delegating responsibility. Skillful supervisors with expertise who were able to provide practical support were particularly appreciated.…”
Section: Previous Reviewsmentioning
confidence: 99%
“…Writers with a behavioral/mental health background (e.g. Spence et al, 2001, Milne, 2010 and social workers in North America who provide clinical social work (i.e. with an emphasis on counseling and psychotherapy) often refer to 'clinical supervision' (Bogo and McKnight, 2006;Renner et al 2009).…”
Section: Definitions and Theoretical Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, there is a view that supervision has become a profession in its own right and learning to become a supervisor is a generic rather than profession-specific process. As such, a need for a common philosophy for clinical supervision has been suggested (Davys & Beddoe, 2008;Mullarkey et al, 2001;Spence et al, 2001). …”
Section: Views About Cross-disciplinary Supervisionmentioning
confidence: 99%
“…The characteristics of adequate supervision are often not understood or sustained and many supervisors lack the knowledge, skills and tools for effective supervision (Marquez & Kean, 2002;Spence, Jill, Kavanagh, Strong, & Worrall, 2001). Involving the broader workforce in supervision (i.e., both supervisors and peer colleagues) can reduce workload for supervisors, promote practitioner self-regulation and skill development, and build organization capacity .…”
Section: Resultsmentioning
confidence: 99%